PERLAKUAN AKUNTANSI PENDAPATAN PADA AHASS MIRA MOTOR DI GIANYAR - I Made Suartika; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2020)
Accounting standards provide guidelines for the accounting treatment of an event. These guidelines are reflected in the definition, measurement, evaluation, recognition and disclosure of elements or financial statement items. AHASS Mira Motor is a company engaged in the business of trading and services whose business activities are selling motorcycle parts. The purpose of this study was to analyze the accounting treatment of income on AHASS Mira Motor Gianyar in accordance with ETAP financial accounting standards. The results of the study found that revenue recognition on AHASS Mira Motor Gianyar did not conform to ETAP financial accounting standards regarding revenue, revenue measurement on AHASS Mira Motor Gianyar were in accordance with ETAP financial accounting standards on revenue, and disclosure of income on AHASS Mira Motor Gianyar did not comply with standards ETAP financial accounting of income.